CRITICAL RECEPTION OF EXISTENTIAL PROSE OF THE INTERWAR DECADES IN UKRAINIAN LITERARY CRITICISM - Devdiuk, Ivanna (Philological Treatises, 2020)
The article deals with peculiarities of critical expierence of existential problems in the interwar Ukrainian prose works. The topicality of the article is caused by the lack of special studies on this problem. Its purpose is to determine the evolution and stages of the scientific-critical reception of existential discourse in the Ukrainian writing of the named period. In the course of the analysis it has been revealed that the first positive reviews, which emphasize the intellectual and psychological dominant of the works, date back to the twentieth years marked by the relative freedom of self-expression. From the 1930s to the end of the 1980s the works of modernist writers almost completely disappear from the scientific and reading space. In this paper it is emphasized a situation in a totalitarian society where criticism, serving the dominant ideology, acquires the characteristics of a political structure. Ignoring the fact of the functioning of modernism in Ukrainian culture meant a simultaneous turning away from the manifestations of artistic representation of individual existence. Artificially interrupted process has been compensated by literary studies of the representatives of Ukrainian diaspora which underline a high level of prose works by M. Khvylovy, V. Pidmohylny, V. Domontovych etc., their congeniality with European writing. The third stage dates back to the nineties and continues to this day. It is marked by the study of Ukrainian literature from the point of view of the latest methodologies. One of the research areas is reading texts in the projection of the philosophy of existence. The analysis of critical works proves the notable progress of our scholars towards the comprehension of existentiality as a historically and culturally determined phenomenon in the Ukrainian art space. Existential discourse is unanimously regarded as an organic component of modernist processes, marked by the shift of attention from the external reality to the internal life. of The literary critics active search has resulted both in the diversity of the scientific and methodological spectrum of research and the broadening of the visions of the artistic and aesthetic context in which this discourse operates.